2002
DOI: 10.1074/jbc.m112277200
|View full text |Cite
|
Sign up to set email alerts
|

AKAP350 at the Golgi Apparatus

Abstract: AKAP350 can scaffold a number of protein kinases and phosphatases at the centrosome and the Golgi apparatus. We performed a yeast two-hybrid screen of a rabbit parietal cell library with a 3.2-kb segment of AKAP350 (nucleotides 3611-6813). This screen yielded a full-length clone of rabbit chloride intracellular channel 1 (CLIC1). CLIC1 belongs to a family of proteins, all of which contain a high degree of homology in their carboxyl termini. All CLIC family members were able to bind a 133-amino acid domain with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…This could result from activation of the chloride channel in pump containing membranes or physical approximation of the active channel and pump. Previously CLIC-4 and -5 proteins and the v-H ϩ -ATPase have been shown to associate with cytoskeleton proteins that are c-Src substrates (42,78,85). In these studies the proton pump is found in cytoskeletal-associated vesicles while the soluble CLIC-proteins directly interact with F-actin-based structures.…”
Section: Volume 281 • Number 38 • September 22 2006mentioning
confidence: 91%
“…This could result from activation of the chloride channel in pump containing membranes or physical approximation of the active channel and pump. Previously CLIC-4 and -5 proteins and the v-H ϩ -ATPase have been shown to associate with cytoskeleton proteins that are c-Src substrates (42,78,85). In these studies the proton pump is found in cytoskeletal-associated vesicles while the soluble CLIC-proteins directly interact with F-actin-based structures.…”
Section: Volume 281 • Number 38 • September 22 2006mentioning
confidence: 91%
“…For example, CLIC3 was originally discovered as a binding partner for ERK7, a member of the mitogen-activated protein kinase family [18], and bovine p64 has been shown to associate directly with p59 fyn , a Src family tyrosine kinase [19]. In addition, multiple CLIC family members can associate with AKAP350, a scaffolding protein that sequesters cAMP-dependent protein kinase and several other protein kinases and phosphatases to particular subcellular sites [16,17]. More recently, CLIC6 has been shown to bind scaffolding proteins, such as radixin and multi-PDZ protein, as well as dopamine D 2 -like receptors [24].…”
Section: Discussionmentioning
confidence: 99%
“…CLICs constitute a new family of putative chloride channel proteins with several distinct members, including bovine p64 and human CLIC1-6 [10,11]. CLIC proteins are localized to a variety of subcellular compartments in various cell types, and although they have been implicated in chloride ion transport [12,13], several reports show that certain family members can associate with the cytoskeleton, scaffolding proteins, and signaling enzymes [14][15][16][17][18][19]. The identification of multiple CLIC proteins in spermatozoa, which may interact with PP1c2, opens a new area of study on the role of CLICs in sperm function.…”
Section: Introductionmentioning
confidence: 99%
“…CLIC4 has several consensus phosphorylation sites, and it interacts with a 14-3-3 isoform (14). Furthermore, recent evidence indicates that CLIC family members interact with the AKAP350 chaperone protein (26). p64 is a substrate for the Fyn kinase (27), and CLIC3 associates with ERK7 (3).…”
Section: Mtclic/clic4 Nuclear Translocation Initiates Apoptosismentioning
confidence: 99%